(untitled) (ModaPalavra e-periódico, 2024)
This paper aims to discuss the production of emotions in fashion consumption, focusing on laughter. The media event that instigated us were parodies about the look presented by Kim Kardashian at the Paris Fashion Week in 2022. Kardashian attended the event dressed in tapes with the logo of the luxury brand Balenciaga becoming the subject of memes on social networks. The research problem that instigated us concerns: what is the role of laughter as emotion in the fabrication of meanings about fashion in a context of interaction via social networks? We developed an exploratory research from a case study, using a documental survey, with a qualitative approach, having as empirical object publications made on Instagram. We employ an interdisciplinary look and a theoretical framework that includes readings of anthropology of emotions, fashion and communication.